Edible plant extracellular vesicles: An emerging tool for bioactives delivery - Fan, Shi-Jie; Chen, Jia-Ying; Tang, Chao-Hua; Zhao, Qing-Yu; Zhang, Jun-Min; Qin, Yu-Chang (Frontiers in Immunology, 2022)
The extracellular vesicles (EVs) in edible food have a typical saucer-like structure and are nanoparticles released by numerous cells. They have different components and interact with other biological samples in diverse ways. Therefore, these nanoparticles could be used to develop bioactives delivery nanoplatforms and anti-inflammatory treatments to meet the stringent demands of current clinical challenges. This review aims to summarize current researches into EVs from edible plants, particularly those that can protect siRNAs or facilitate drug transportation. We will discuss their isolation, characterization and functions, their regulatory effects under various physiological and pathological conditions, and their immune regulation, anti-tumor, regeneration, and anti-inflammatory effects. We also review advances in their potential application as bioactives carriers, and medicinal and edible plants that change their EV compositions during disease to achieve a therapy propose. It is expected that future research on plant-derived EVs will considerably expand their application.